Leveraging Digital Transformation for Performance Management: A Case Study on E-Sakip Implementation in Government Institutions - Monika Handayani; Mohammad Arliyan Syahrial (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The integration of digital transformation into government agencies' performance management has become essential in enhancing public service delivery, efficiency, and accountability. This study focuses on implementing the Electronic System for Government Agency Performance Accountability (E-SAKIP) in Indonesia as a case study of digital transformation. The research employs a qualitative approach with a case study design to explore the effectiveness, challenges, and impact of E-SAKIP on performance management. The findings indicate that E-SAKIP has significantly improved transparency and efficiency in government operations, reducing time and costs associated with performance reporting by up to 70%. However, challenges such as inadequate infrastructure, resistance to change, and insufficient training for government employees have hindered its full potential. The study underscores the need for ongoing support, including enhanced infrastructure, continuous training, and stronger leadership to ensure successful digital transformation. These insights offer valuable recommendations for further development of E-SAKIP and similar systems in other government contexts.